Avaliação do desempenho dos equipamentos mamográficos e da qualidade das imagens em Serviços de Saúde do Município de São Paulo - Ruberti Filha, Eny Moreira [UNIFESP] (2011)
Objective: Verify equipment performance and image quality according to National and European test protocols. Identify the essential quality control test set that can be performed in the mammography services in order to guarantee quality in the imaging acquisition and reading process. Methods: Firstly, were evaluated the performance tests of five mammographic equipment of the public facilities. The signal detection was verified by Alvim statistic phantom and kappa value was measured in consonance with the specialist. Secondly, five weeks of consecutive tests were performed relating the film processing, the reference optical density (OD) constancy and the AEC performance. The CIRS phantom quality images were analyzed and the entrance surface air kerma (ESAK) was performed with TLD dosimeters. Thirdly, tests were replicated in thirteen mammography units. At this step, CIRS phantom images were digitalized and contrast and noise parameters were evaluated. The average glandular dose (MGD) was also calculated. Fourthly, the quality check tests were performed in two digital mammography equipment (DR) of private facilities and two conventional mammography equipment units connected with computerized radiography system(CR) installed in the public health facilities. Results: The equipment performance presented satisfactory results, except for the HVL, AEC and film processing. The Alvim phantom images were analyzed in a teleradiology facility by specialists and the results of the fiber and microcalcification detection were unacceptable, except for a single one. On the first reading, the kappa values varied from 0.02 to 0.68, being kappa for the microcalcifications from 0.26 to 0.6 and kappa for fibers from 0.06 to 0.76. On the second one, the kappa values were statistically superior. The mean glandular dose was 1.95mGy (0.65-3.5) and the OD measurements varied from 1.54 to 1.85. The five weeks tests results related to the film processing, OD constancy and AEC performance were unacceptable. The mean ESAK result was 9.33mGy (6.54-17.26), OD was 1.84(1.05-2.46), developer and fixer temperatures varied from 30.8 to 470C and 21 to 640C, respectively. On the third step, the MGD calculated for 4.5cm breast thickness varied from 1.0 to1.8mGy and 2.43 to 4.95mGy for 6.5cm breast thickness. The kappa values varied from 0.34 to 0.63, being kappa for microcalcification from 0.32 to 0.71 and kappa for fibers from 0.40 to 0.68. In this period, the OD analysis presented values below 1.4 that suggested a subprocessing image. The SNR varied from 5.9 to 24, 6% and 6.0 to 24, 6% for 4.5 and 6.5cm breast thicknesses, respectively. Conclusion: The methodology allowed verifying the importance of controlling process since the generation until the image analysis by the specialist. This control must be performed more often than required by the Brazilian law. It has become necessary to introduce the MGD calculation in the quality assurance program nationwide. The image analysis performed at the teleradiology facilities showed the need of diagnosis language standardization, as well as the viewing conditions. Clearly, the tests frequency showed that inadequate film processing is a recurring item and also contributes effectively for the quality image reduction.